A fire in the sky : a novel - Jordan, Sophie (Avon, an imprint of HarperCollinsPublishers, 2024)
"Dragon fire no longer blisters the skies over Penterra, but inside the lavish palace, life is still perilous...especially for Tamsyn. Raised in the glittering court alongside the princesses, it's her duty to be punished for their misdeeds. Treated as part of the royal family but also as the lowliest servant, Tamsyn fits nowhere. Her only friend is Stig, Captain of the Guard...though sometimes she thinks he wants more than friendship. When Fell, the Beast of the Borderlands, descends on her home, Tamsyn's world becomes even more dangerous. To save the pampered princesses from a fate worse than death, she is commanded to don a veil and marry the brutal warrior. She agrees to the deception even though it means leaving Stig, and the only life she's ever known, behind. The wedding night begins with unexpected passion--and ends in near violence when her trickery is exposed. Rather than start a war, Fell accepts Tamsyn as his bride...but can he accept the dark secrets she harbors--secrets buried so deep even she doesn't know they exist? For Tamsyn is more than a royal whipping girl, more than the false wife of a man who now sees her as his enemy. And when those secrets emerge, they will ignite a flame bright enough to burn the entire kingdom to the bone. Magic is not dead...it is only sleeping. And it will take one ordinary girl with an extraordinary destiny to awaken it."--